Development of quality culture in construction firms: the role of leadership and human resource management - Wan Mahmood, Wan Yusoff; Mohammed, Miswan @ Abdul Hakim; Abdullah, Mat Naim; Misnan, Mohd Saidin; Mahmud, Syamsul Hendra (2008)

(untitled)
Total quality management (TQM) has the potential to improve business results, greater customer satisfaction, worker involvement, team working and better management of workers within organisation. However, many organisations have been continually struggling with its implementation. The successful TQM implementation within the organization requires a cultural change and it being recognised as an important aspect of total quality development. Total quality is a holistic concept, and requires the motivation of all members of an organisation to seek customer satisfaction. Hence, the aspects of leadership and human resource management (HRM) are to be considered for the development of quality culture in organisation. Leadership and HRM can reinforce human relationship and group consciousness, raise employee competence, create positive job attitudes, provide a condusive work culture and achieve culture change. Therefore, they act as the catalyst for the implementation of TQM. The paper will discuss in general, the factors that influence the development of quality culture in organisation. Further, its will discuss how the leadership and HRM factors can help for a quality cultural shift in an organisation.